A Proposed Culture-Based Model for Elementary School Social Studies Teachers’ ‎Perceptions of Bullying Cases in Kuwaiti Government Schools - Al-Shammari, Abdulaziz (Jordan Journal of Educational Sciences, 2024)
This study aimed to prepare a proposed culture-based model for primary school social studies teachers’ perceptions of bullying cases in public schools in Kuwait. The study sample consisted of (200) female social studies teachers in elementary schools. The study results showed that the ratio between applying the social studies curriculum in elementary schools and bullying incidents in Kuwait was weak. Social studies teachers are not satisfied with the social studies curriculum in terms of its suitability for the intellectual levels of students and its role in preparing good learners. The study recommended the need for curricula planners to keep up with modern psychological and educational trends in reducing the incidence of bullying in schools and for curricula developers to benefit from the results of this study by taking some measures to reduce cases of bullying